2023
DOI: 10.1021/jacs.2c11373
|View full text |Cite
|
Sign up to set email alerts
|

The Fluorocarbene Exploit: Enforcing Alternation in Ring-Opening Metathesis Polymerization

Abstract: Fluoroalkenes are known to be notoriously reluctant substrates for olefin metathesis due to the generation of thermodynamically stable Fischer-type fluorocarbene intermediates, which invariably fail to undergo further reaction. In the present disclosure, we find that fluorine substitution on the sp 2 carbon also strictly suppresses homopolymerization of norbornene derivatives (NBEs), and this can be harnessed to achieve alternating ring-opening metathesis polymerization (ROMP) with an appropriately electron-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Surprisingly, examples of ROM of fluorinated substrates are extremely scarce, polymerization of fluorinated norbornene derivatives being the only known example [19] . Simultaneously with our work, a ROCM of ethyl vinyl ether with norbornene derivatives bearing fluorine atoms on the sp 2 carbons was studied and very recently published [20] …”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Surprisingly, examples of ROM of fluorinated substrates are extremely scarce, polymerization of fluorinated norbornene derivatives being the only known example [19] . Simultaneously with our work, a ROCM of ethyl vinyl ether with norbornene derivatives bearing fluorine atoms on the sp 2 carbons was studied and very recently published [20] …”
Section: Introductionmentioning
confidence: 61%
“…[19] Simultaneously with our work, a ROCM of ethyl vinyl ether with norbornene derivatives bearing fluorine atoms on the sp 2 carbons was studied and very recently published. [20] The presence of fluorine atoms in a molecule modifies its properties and thus fluorinated compounds found wide applications as pharmaceuticals, [21] agrochemicals [22] or biomolecules. [23] Increasing attention is paid to compounds bearing a tetrafluoroethylene unit.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29] In the study of branched or polar olefin polymers, researchers found that large steric ligands increased the rigidity, limited the rotation, and improved electron donating to catalysts, giving the catalysts good thermal stability, long life, good selectivity, and less chain transfer, so such catalysts had high catalytic activity and high molecular weight. [30][31][32][33] For example, Long et al synthesized αdiimide Ni complex with 2,6-diphenyl-substituted aniline, and this catalyst had very good thermal stability and could efficiently catalyze ethylene polymerization at 100 °C. Moreover, the existence of this large steric aromatic ring could effectively inhibit the chain transfer reaction, devoting to a narrow molecular weight distribution (M w /M n < 1.5) under high temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This innovation provides rapid access to copolymers with well-defined backbone sequences 12,13 and copolymers with backbone degradability. 14,15 AROMP has been used to create materials with unique and interesting properties. 12,13,16 However, in order to create more advanced functional materials using AROMP, it is important that we understand the kinetics of the ring openings of the bicyclooctene and the subsequent ring opening of CH.…”
mentioning
confidence: 99%
“…Hence, ROMP has been limited to high strain energy monomers such as norbornenes, cyclooctadienes, and cyclobutenes. However with recent developments and innovations, low strain cyclic olefins such as cyclohexene (CH), which traditionally is impractical for ROMP, can be incorporated into alternating copolymers via ROMP (AROMP) and cascade enyne metathesis polymerization. When CH is combined with specific monomer types that undergo only a single metathesis cycle and do not homopolymerize, the monomers will cross-react to form precisely alternating copolymers. Bicyclooctenes , and disubstituted cyclopropenes are prominent examples of single addition monomers that can form highly alternating copolymers with cyclohexene and other low strain cyclic olefins. This innovation provides rapid access to copolymers with well-defined backbone sequences , and copolymers with backbone degradability. , …”
mentioning
confidence: 99%